The Effect of Aluminium Content on the Bioactivity Behaviour of Magnesium Alloys for Biomedical Applications - Nur Maizatul Shima, Adzali (EDP Sciences, 2020)
Link to publisher's homepage at https://www.matec-conferences.org/